Editorial: Theme issue on the ecology of soil microorganisms - Baldrian, Petr; Pennanen, Taina; Kohout, Petr; Fritze, Hannu (FEMS microbiology ecology, 2024)
Inoculation of common bean seed with diversified bacterial synthetic communities can induce deep modifications of both seed and seedling microbiota, even in living potting soil.
Keywords: Soil Microbiology; Ecology; půdní mikrobiologie; ekologie